2019
DOI: 10.2503/hortj.utd-032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of <i>S-RNase</i>-homologous Genes Expressed in Styles in ‘Hyuganatsu’ (<i>Citrus tamurana</i> hort. ex Tanaka)

Abstract: In this study, S-RNase-homologous genes expressed in styles were isolated from a gametophytic selfincompatible citrus cultivar, 'Hyuganatsu'. Sweet orange and clementine genome databases were searched to identify 13 ribonuclease T2 (T2 RNase) genes. Further blast searches using citrus EST databases were conducted with these 13 sequences as queries to obtain five additional EST sequences. Known T2 RNase genes, including the S-RNases of Rosaceae, Solanaceae, and Plantaginaceae were retrieved from the public data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Thus, they are considered distinct from S-RNases (Honsho et al, 2021). The previously reported homologous genes of S-RNase, CtRNS1 (Honsho et al, 2019b) and CgRNS3 (Liang et al, 2017), were placed in low polymorphic subclusters 1 and 2, respectively, both of which are non-S-RNase subclusters (Fig. 2).…”
Section: Features Of Citrus S-rnasementioning
confidence: 87%
See 2 more Smart Citations
“…Thus, they are considered distinct from S-RNases (Honsho et al, 2021). The previously reported homologous genes of S-RNase, CtRNS1 (Honsho et al, 2019b) and CgRNS3 (Liang et al, 2017), were placed in low polymorphic subclusters 1 and 2, respectively, both of which are non-S-RNase subclusters (Fig. 2).…”
Section: Features Of Citrus S-rnasementioning
confidence: 87%
“…It is reasonable to hypothesize that citrus SI is based on the S-RNase system because several phenotypic features of citrus SI, such as pollen tube behavior in the SI reaction, are similar to those of known S-RNase-based GSI plants. The S-RNase homologs from citrus plants were cloned after overcoming many challenges (Chai et al, 2011a;Honsho et al, 2019b;Liang et al, 2017;Miao et al, 2011a). Although some genes did not show tissue-specific expression (Chai et al, 2011a;Miao et al, 2011a), indicating that they are inappropriate as S-RNase genes, Liang et al (2017) identified a tissuespecific S-RNase homolog, named CgRNS3, from 'Shatian' pummelo based on information obtained from the genome sequence of sweet oranges (Xu et al, 2013).…”
Section: Female Determinant Of Citrus Self-incompatibility Is the S-r...mentioning
confidence: 99%
See 1 more Smart Citation
“…In ‘Shatian’ pummelo ( C. grandis ), CgRNS3 possessed several common characteristics of the pistil determinant of SI and was specifically expressed in pistil ( Liang et al, 2017 ), however, it was not anchored into the S-locus ( Liang et al, 2020 ). Pistil-specific CtRNS3 from Citrus tamurana showed S 1 -genotype-dependent in different cultivars, implying that CtRNS3 may serve as the S 1 - gene ( Honsho et al, 2019 ). Liang et al (2020) studied the S-locus in pummelo and concluded that S-RNase and SLF mediate SI reaction in Citrus .…”
Section: Introductionmentioning
confidence: 99%
“…In 'Shatian' pummelo (C. grandis), CgRNS3 possessed several common characteristics of the pistil determinant of SI and was specifically expressed in pistil (Liang et al, 2017), however, it was not anchored into the S-locus (Liang et al, 2020). Pistil-specific CtRNS3 from Citrus tamurana showed S 1 -genotype-dependent in different cultivars, implying that CtRNS3 may serve as the S 1-gene (Honsho et al, 2019). Liang et al (2020) studied the S-locus in pummelo and concluded that S-RNase and SLF mediate SI reaction in Citrus.…”
Section: Introductionmentioning
confidence: 99%